2003
DOI: 10.1093/humrep/deg414
|View full text |Cite
|
Sign up to set email alerts
|

Galactose toxicity in the rat as a model for premature ovarian failure: an experimental approach readdressed

Abstract: Experimental galactose toxicity may serve as a model for exploring some of the basic tenets of POF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 33 publications
7
90
1
1
Order By: Relevance
“…For instance, in fertility clinic populations (11), the timing of dietary assessment may have been several months or years after the diagnosis of infertility, whereas for most women in this cohort, diet was assessed soon after conception attempts began and before the diagnosis of infertility. Our study agrees with most (10, 11) but not all (8) previous studies in providing support against the hypothesis of ovarian toxicity via galactose-lactose pathways (2)(3)(4).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For instance, in fertility clinic populations (11), the timing of dietary assessment may have been several months or years after the diagnosis of infertility, whereas for most women in this cohort, diet was assessed soon after conception attempts began and before the diagnosis of infertility. Our study agrees with most (10, 11) but not all (8) previous studies in providing support against the hypothesis of ovarian toxicity via galactose-lactose pathways (2)(3)(4).…”
Section: Discussionsupporting
confidence: 92%
“…3 Adjusted for total energy intake. 4 Adjusted for total energy intake, age, BMI, smoking history, parity, alcohol intake, physical activity, last method of contraception, and regular multivitamin use. PRESTO models were additionally adjusted for race/ethnicity and education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An animal study found significantly lower concentrations of estradiol and elevated FSH and LH concentrations in rats fed high amounts of galactose, a breakdown component of lactose, compared with controls (14). In addition, progesterone concentrations were significantly decreased in rats after lactose treatment, whereas no differences were found in serum concentrations of estradiol (13).…”
Section: Discussionmentioning
confidence: 97%
“…The biological mechanisms that support an association between dairy food intake and ovulatory function are largely unknown. However, impaired ovarian function was observed in rats fed excessive amounts of lactose (13) and galactose (14), which points to potential biological pathways. These results highlight the need for further study of dairy food intake and reproductive function, particularly among healthy women.…”
Section: Introductionmentioning
confidence: 99%